Pengembangan Instrumen Matematika Dengan Soal Essay Pada Materi Bilangan Pecahan Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Kelas VII MTs Karya Utama - Patimah Hasibuan; Fitri Harabiyah Gultom; Windi Veber Yanti Sembiring; Riski Parubahan Harahap; Rizki Wahyudi Nasution; Nur Saniyah Siregar; Mia Hafizah Tumangger (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Research and development is a test model that is expected to determine these holes. Instruments are tools used to collect information or data. Assessment is a movement to obtain data about how something functions, which is then used to determine ideal decisions in navigation. Characterizes assessment as an evaluation cycle that is linked to student implementation and work results. Before making a decision, evaluation is the process of determining what information is needed and collecting and utilizing that information. Advanced research strategies are techniques used to create specific items and assess their adequacy. Then again, to make a particular item, it is necessary to investigate the needs and test the suitability of the item. Innovative punishment embraces rationality and convenience simultaneously. Inventive reasoning can be considered as a combination of consistent and differentiated reasoning to produce something new. This oddity indicates imaginative reasoning in arithmetic, whereas the different signs are associated with coherent and differentiated reasoning.